1980
DOI: 10.1002/hlca.19800630412
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of 3,5‐Diamino‐1,2,4‐oxadiazoles. 2nd Communication

Abstract: SummaryThe 5-amino-3-arylamino-1,2,4-oxadiazoles 2 are conveniently prepared by oxidative cyclization of the arylamidinoureas 10. The process is also capable of producing a variety of the 5-substituted-amino analogs 32 when the appropriately substituted guanidine 31 is employed as the substrate. Two different types of rearrangement leading to triazol-3-ones accompany cyclization depending on the choice of starting material. The structures of the rearranged products were established by X-ray crystallographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Only one report in the literature has described this unusual ring system, and recently, a related five-membered cyclic amidinourea was found in an antitumor antibiotic NA22598 . All of the published methods, which includes the reaction of guanidines with isocyanates, hydrogenation of 5,3-diamino-1,2,4-oxadiazoles, or the hydrolysis of cyanoguanidines under strongly acidic conditions, are either inefficient, involve harsh reaction conditions, or require numerous steps . We have examined and subsequently determined that none of these methods were suitable for accessing the labile TAN-1057 amidinourea substructure.…”
Section: Resultsmentioning
confidence: 99%
“…Only one report in the literature has described this unusual ring system, and recently, a related five-membered cyclic amidinourea was found in an antitumor antibiotic NA22598 . All of the published methods, which includes the reaction of guanidines with isocyanates, hydrogenation of 5,3-diamino-1,2,4-oxadiazoles, or the hydrolysis of cyanoguanidines under strongly acidic conditions, are either inefficient, involve harsh reaction conditions, or require numerous steps . We have examined and subsequently determined that none of these methods were suitable for accessing the labile TAN-1057 amidinourea substructure.…”
Section: Resultsmentioning
confidence: 99%
“…5 Shortly later, Tilley et al 4 reinvestigated that N 2 -chloro-N 1 -methoxycarbonyl-N 3 -phenylguanidine (2a) gave corresponding 1,2,4-oxadiazole as reported by Goetz et al 3 and they suggested that N 1 -alkoxycarbonyl-N 2 -chloro-N 3 -substituted guanidines in which the N 3 -alkyl derivative underwent rearrangement, whereas the corresponding N 3 -aryl derivative cyclized with essentially no rearrangement. They also suggested that electron-withdrawing groups on the aromatic ring of the N 3 -aryl-N 1 -carbamoylguanidines (3) seemed to favor 1,2,4-oxadiazole formation.…”
mentioning
confidence: 88%
“…The N-substituted cyanoguanidines formed (typically in refluxing ethanol), are able to further react with another amine, as described above in the dedicated section. However, there are a few counter examples where the addition of the amine took place on the cyano group first: by using trimethylsilylamines [74], activation of the thiomethyl group by Cu(I) [75], or in case of consequent steric hindrance in the vicinity of the isothiourea carbon atom [76] (Scheme 36).…”
Section: Addition Of Amines To N 1 -Cyano-s-methylisothioureas (Pathway D)mentioning
confidence: 99%